Magic Boom Chemical: A Tracking Marker-Based Approach in Developing Chemical Molecule Textbook - Tina Tri Wulansari; Pebiansyah Hafsari; Ratih Fenty Anggriani Bintoro; Yuli Fitrianto; Gunawan Gunawan; Nyoman Santiyadnya; Reza Andrea; Syafei Karim; Dewi Rostia; Guntur Arie Wibowo; Tri Hannanto Saputra; Maria Floriana Ping (Journal of Applied Engineering and Technological Science)
In Traditional teaching methods for chemical molecules, which rely on textbooks and physical modeling tools, face challenges in providing an engaging and comprehensive learning experience. This study introduces "Magic Boom Chemical," an augmented reality (AR)-based educational tool utilizing marker tracking to display three-dimensional molecular structures. A quasi-experimental method was employed, involving two groups of high school students: an experimental group using the AR application and a control group using conventional teaching methods. Pre-tests and post-tests were conducted to assess the effectiveness of the tool. Results indicated a significant improvement in students’ understanding and engagement when using the AR-based media, with the experimental group achieving higher average post-test scores. The study concludes that integrating AR into educational materials can enhance learning outcomes and increase students’ motivation. These findings highlight the potential of AR technology as an innovative solution for improving science education and suggest further research to refine and expand its applications.